Near Neighbours, Distant Brothers: The Inter-Monastic Networks of Benedictine Houses in the Southern Low Countries (900-1200) - Snijders, Tjamke (Medieval Liège at the Crossroads of Europe. Monastic Society and Culture, 1000-1300, 2017)
(als e-book: 978-2-503-56897-3)